Keteladanan Kepemimpinan Paulus dan Implikasinya bagi Pemimpin Masa Kini - Boyman Aspirasi Zebua; Claudia Angelina; Monica Santosa (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
Paul was one of the biblical figures who had a leadership pattern that was widely praised for being effective and able to lead the congregation he served well. However, there are still many Christians who doubt him. In the end, the Apostle Paul's leadership was interpreted as materialistic leadership even though the Bible itself clearly states that Paul was an exemplary leader both physically and spiritually, but still they did not recognize Paul's leadership. Therefore, it is very important to have an understanding of Paul's exemplary leadership, especially when experiencing moments in leading the churches served. The purpose of this study is to answer and discuss Paul's exemplary leadership and its implications for today's leaders. The research method used in writing this article is a qualitative method. The findings of this article show that leadership is an inseparable part of human life, where leadership plays an important role for the continuity and journey of human life to get closer and there is an opportunity to glorify God, then become an active missionary in relying on God. Paul's exemplary leadership can be seen in any situation he still relies on God and dares to preach the gospel and strengthen and empower others to do what he did.